Simonas Daukantas’s Phaedrus - Dilytė, Dalia (Senoji Lietuvos literatūra, 2024)
The article offers a detailed analysis of the first translation of the works by Phaedrus, a Roman author of fables, into Lithuanian by Simon Daukantas, highlights the translation principles chosen by Daukantas, discusses the peculiarities of this translation, and points out the strengths and weaknesses of the translation. One of the characteristics of the genre of the fable is the small size of the work, and Phaedrus, in his haste to make his points, very often shortens the text by omitting the words inquit, ait, or similar, which introduce direct speech. Daukantas very rarely adheres to such text shortening ambitions. He inserts the words sako ‘says’, sakė ‘said’, klausė ‘enquired, asked’ etc., which Phaedrus did not use in particular places, much more often. Another feature of Phaedrus’s fables is the tendency to express ideas in an abstract manner. Daukantas approaches this predilection of Phaedrus with caution. When he thinks it is permissible, he sticks to the original but usually gives simple and clear sentences. To make the picture clearer and more specific, the translator sometimes adds additional words. Yet it is important to emphasise that by adding these words to the text, the translator does not introduce new ideas or create new images, so that the accuracy of the translation is not trespassed and the goal of clarity and concreteness is achieved. As for the translation of the morals, it must be stressed that Daukantas diligently preserves the place of Phaedrus’s moral, and thus we see both the introductory and the end-of-fable morals in the translation. The translator did not add morals to the fables that do not have morals in the original. Phaedrus’s morals are usually short: the narrator adds only one or two summarising sentences. Daukantas, while staying loyal to the original, adds nothing to Phaedrus’s text and takes nothing away from it. Daukantas’s principles of translation and cultural adaptation of ancient realities would be the following: in some places he gives Lithuanian equivalents, elsewhere he leaves some realities unchanged, presumably to educate his readers, and in other places he adds explanations about the ancient world. The biggest shortcoming of the translation is that Phaedrus’s versed fables are translated in prose, which means that Daukantas’s text does not have the steady rhythmicity of poetry or the melodic repetition of long and short syllables. On the other hand, although a prose translation of a poetic work would be intolerable nowadays, at that time, in the early days of literature, its appearance was still extremely valuable. In summing up the principles and peculiarities of Daukantas’s translation, we should note that although Daukantas translated Phaedrus’s fables in the middle of the nineteenth century, he turned out to be quite a modern translator, even in line with translation requirements of the twenty-first century: by adhering to the principle of faithfulness to the original text, he neither added anything nor distorted any of the plot lines. As Daukantas often renders the text in a non-literal way and demonstrates great creativity, he occasionally comes close to breaching the boundaries of accuracy of thought and style; nonetheless, he does not cross them. A characteristic feature of Daukantas’s translation style is his quest for clarity and concreteness. Phaedrus’s fables are translated in a very beautiful, rich, folklore-infused Lithuanian language, which is highly suitable for the genre of the fable.